2021
DOI: 10.1016/j.hal.2021.102009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a short-term salinity stress on the growth, biovolume, toxins, osmolytes and metabolite profiles on three strains of the Dinophysis acuminata-complex (Dinophysis cf. sacculus)

Abstract: The three D. cf. sacculus strains tolerated hypo-and hyperosmotic conditions (25 and 42 vs. 35) Higher proline, glycine betaine and DMSP contents of D. cf. sacculus at the highest salinity Growth, biovolume, toxin contents and profiles were not affected by salinity stress Metabolomics showed intraspecific variability of D. cf. sacculus but no clear salinity effect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…These differences may not be apparent in situ; however, because all isolates were grown under the same culturing conditions (i.e., Mid‐Atlantic water used for f/2 medium, 15°C, salinity of 25, 100 μmol photons · m −2 · s −1 PAR, and the same ciliate and cryptophyte prey) rather than under region‐specific conditions or prey‐matched species that could modulate growth rate, biovolume, and toxin production (Basti et al, 2015, 2018; Fiorendino et al, 2020; Gaillard et al, 2021; García‐Portela et al, 2018, 2020; Hattenrath‐Lehmann et al, 2010, 2015; Hattenrath‐Lehmann & Gobler, 2015). Measured growth rates were, therefore, neither optimized nor necessarily reflective of species' behavior in situ.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may not be apparent in situ; however, because all isolates were grown under the same culturing conditions (i.e., Mid‐Atlantic water used for f/2 medium, 15°C, salinity of 25, 100 μmol photons · m −2 · s −1 PAR, and the same ciliate and cryptophyte prey) rather than under region‐specific conditions or prey‐matched species that could modulate growth rate, biovolume, and toxin production (Basti et al, 2015, 2018; Fiorendino et al, 2020; Gaillard et al, 2021; García‐Portela et al, 2018, 2020; Hattenrath‐Lehmann et al, 2010, 2015; Hattenrath‐Lehmann & Gobler, 2015). Measured growth rates were, therefore, neither optimized nor necessarily reflective of species' behavior in situ.…”
Section: Discussionmentioning
confidence: 99%
“…With another well-known harmful algae genus, Dinophysis , the response of their metabolome to salinity stress shows strain-dependent modifications under different salinity concentrations. These results, as well as the absence of effects on growth rate and toxins (okadaic acid and pectenotoxin), suggest that Dinophysis sacculus is resistant to salinity variations [ 29 ]. However, more studies are needed to explore dinoflagellate metabolomic responses to nutrient deficiency and metal contamination, as already implemented with transcriptomic and proteomic approaches.…”
Section: Metabolomic Approachesmentioning
confidence: 99%
“…In culture experiments, PTX2 have been found to affect survival in early larval stages of fish (Rountos et al 2019) and shellfish (Gaillard et al 2021, Pease et al 2022. Furthermore, Li et al (2018) showed in vitro uptake of dissolved DSP toxins by mussels.…”
Section: Introductionmentioning
confidence: 99%